Association study in mexican patients with thyrotoxic hypokalemic periodic paralysis - Bautista Medina, Mario Arturo; Gallardo Blanco, Hugo Leonid; Martínez Garza, Laura Elia; Cerda Flores, Ricardo Martín; Lavalle González, Fernando Javier; Villarreal Pérez, Jesús Zacarías (Spandidos Publications, 2020)
Hypokalemic periodic paralysis type 1 (OMIM; HOKPP1) and type 2 (OMIM; HOKPP2) are diseases of the muscle characterized by episodes of painless muscle weakness, and is associated with low potassium blood levels. Hyperthyroidism has been associated with thyrotoxic periodic paralysis (TTPP) (OMIM; TTPP1 and TTPP2), and genetic susceptibility has been implicated. In the present study, the clinical and epidemiological characteristics of patients with TTPP are described, together with their association with genetic variants reported previously in other populations. A prospective and a retrospective search of the medical records of patients who attended the emergency department at the Hospital Universitario ‘Dr. Jose E. Gonzalez’ in Monterrey, Nuevo León, Mexico, and were diagnosed with TTPP was performed. A total of 16 gene variants in the genes MUC1, CACNA1S, KCNE3 and SCN4A, and nine ancestry informative markers (AIMs), were analysed by Multiplex TaqMan™ Open Array assay, and a genetic association study was performed. A total of 11 patients were recruited, comprising nine males and two females (age range, 19‑52 years) and 64 control subjects. Only two cases (18%) had a previous diagnosis of hyperthyroidism; the rest were diagnosed subsequently with Graves' disease. Based on the analysis, two DNA variants were found to potentially confer an increased risk for TTPP: S1PR1 rs3737576 [odds ratio (OR), 4.38; 95% confidence interval (CI), 1.08‑17.76] and AIM rs2330442 (OR, 4.50; 95% CI, 1.21‑16.69), and one variant was suggested to be possibly associated with TTPP, namely MUC1 rs4072037 (OR, 3.08; 95% CI, 0.841‑1.38). However, there were no statistically significant associations between any of the 24 DNA variants and TTPP in a population from northeast Mexico.